USULAN PERANCANGAN ALAT BANTU UNTUK MENGURANGI RISIKO CEDERA MUSCULOSKELETAL PADA PEKERJA DI CV. XYZ - Armijal, Armijal; Wahyuni, Dini; Tambunan, Mangara (Jurnal Sistem Teknik Industri, 2018)
Workers involving in a manual task (e.g. lifting, pushing, pulling, etc.) are subject to a musculoskeletal disorders (MSDs) risk. The risk is even worse should the workers are not working in a good body posture while facilities and working environment are not ergonomically designed. Thus, it becomes significant for the workers to have a normal body posture while performing tasks. In addition, they also should be equipped with facilities and working environments that are ergonomically designed. CV. XYZ is a garment industry which produces apparels and other clothes. CV. XYZ has several work stations, and one of them is a film-making (screen printing) station. There are 20 work elements in this station, where all of them are a manual task. This research aims to investigate and evaluate over working condition, facilities and working environment at film-making station which later will be quantified into MSDs risk level. For this purpose, this research will employ Rapid Entire Body Analysis (REBA) to measure MSDs risk of the worker in this station. From this evaluation, it will suggest a creation of ergonomic aid tools which aims to reduce the risk of MSDs level. Those aid tools are a desk, a chair and a lorry that are designed by considering body posture and anthropometry principles. A simulation analyisis will be performed by using a mannequin pro software so that the comparison of the MSDs risk level prior and after the improvement can be obtained. Research finding shows that after implementing the suggested solution, 15 out of 20 work elements show a reduction of REBA score, and lowering the risk of MSDs.